Nonaudit services, audit committee characteristics and accruals quality in Malaysia - Wan Zurina Nik Abdul Majid; Effiezal Aswadi Abdul Wahab; Hasnah Haron; Dian Agustia; Mohammad Nasih (Emerald Publishing Limited, 2021)
The study examines the relationship between nonaudit services (NAS) and accruals quality in Malaysia. The study also considers several important characteristics of audit committee as the determinant for accruals quality. Next, the study examines whether these characteristics mitigate the relationship between NAS and accruals quality.The study employs descriptive analysis, univariate tests and multivariate regression to investigate the potential effect of NAS on acruals quality. Data for audit committee characteristics were hand collected from annual reports downloaded from Bursa Malaysia's website.Based on 1,118 firm-year observations for the period 2009–2011, the study finds that NAS negatively impact accruals quality. This empirical result indicates that the economic bond that is created between auditors and clients restricts the auditors from performing their duty objectively. A fully independent audit committee weakens the negative relationship between NAS and auditor independence.The sample period represents a limitation since it only covers three years of data. This limitation is largely driven by the nature of data collection of NAS fees.These results contribute to Malaysia's policy deliberation to account for the effects of NAS on auditor independence and the oversight role of an audit committee. This study contributes to theoretical perspectives on accruals quality and corporate governance in Malaysia.The novelty of this research, coupled with institutional data in Malaysia, claims the originality of this research.